# Juri

Popular questions and responses by Juri-
## Algebra

Factor out 8x^3y^6 + 27 One factor is 2xy^2+3. (The sum of the cube roots of the first and last terms). Use long division to compute (8x^3y^6 + 27)/(2xy^2 + 3) to get the other factor

*asked on August 6, 2007* -
## Algebra

Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a)(U^2- aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes? a^3+b^3= ????

*asked on August 9, 2007* -
## Algebra

Simplify (b^3)(ab-1)((ab)^2+ab+1) Hint: The last two factors sure look like the difference of two cubes to me. Have you tried that?

*asked on August 9, 2007* -
## Algebra

Divide 1-125b^3 by 5b - 1 You need to learn the technique of polynomial long division. It's just the same as if numbers were involved. See http://www.sosmath.com/algebra/factor/fac01/fac01.html for sevaral examples. Hint: It will be a three-term

*asked on August 6, 2007* -
## Algebra II

Factor out: 1-125b^3 5b -1 is one of the factors. (Consider that an informed guess). Divide that into 1-125b^3 for the other (binomial) factor.

*asked on August 5, 2007* -
## Algebra II

Factor out: 64x^3 + 1 It is a binomial times a trinomial (4x+1)(16x^2-4x+1) should work. Check my math again! [8x^(3/2) - i][8x^(3/2) + i] Although my previous answer works (if i = sqrt-1), Taasha's is what you are looking for.

*asked on August 4, 2007* -
## Algebra 2

Using synthetic division: x^3 + 4x^2 - 3x - 12 / x^2 - 3 Write it out like a long division problem. x^-3 goes into x^3 + 4x^2 -3x -12x times. This is the first term of the answer. Multiply x by x^2 -3 and write the product under the dividend. That would be

*asked on August 3, 2007* -
## Algebra II

(2x^2 + 10x + 12) divided by (x + 3) your question is (2x^2 + 10x + 12)/(x + 3) =2(x+2)(x+3)/(x+3) = can you take it from here?

*asked on July 30, 2007* -
## Algebra

How do I factor out: 21 - 4x - x^2 x^2 + 4x - 21 = 0 this is of the form (ax + c)(bx + d) = abx^2 + (c+d)x + cd here ab = 1 so c+d = 4 cd = -21 therefore c = 7 and d = -3 (x + 7)(x-3)=0 x = -7 and x = 3

*asked on July 29, 2007* -
## Algebra

There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You can decide which is

*asked on July 23, 2007*